Immunometabolic control of trained immunity (2020)
Innate immune cells can adopt long-term inflammatory phenotypes following brief encounters with exogenous (microbial) or endogenous stimuli. This phenomenon is named trained immunity and can improve host defense against (recurrent) infections. In contrast, trained immunity can also be maladaptive in the context of chronic inflammatory disorders, such as atherosclerosis. Key to future therapeutic exploitation of this mechanism is thorough knowledge of the mechanisms driving trained immunity, which can be used as pharmacological targets. These mechanisms include profound changes in intracellular metabolism, which are closely intertwined with epigenetic reprogramming at the level of histone modifications. Glycolysis, glutamine replenishment of the tricarboxylic acid cycle with accumulation of fumarate, and the mevalonate pathway have all been identified as critical pathways for trained immunity in monocytes and macrophages. In this review, we provide a state-of-theart overview of how these metabolic pathways interact with epigenetic programs to develop trained immunity.